2012
DOI: 10.1016/j.mayocp.2012.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiectomy vs Medical Management in Patients With Relapsing Pericarditis

Abstract: Objective: To determine whether surgical pericardiectomy is a safe and effective alternative to medical management for chronic relapsing pericarditis. Patients and Methods: Retrospective review of 184 patients presenting to the Mayo Clinic in Rochester, Minnesota, from January 1, 1994, through December 31, 2005, with persistent relapsing pericarditis identified 58 patients who had a pericardiectomy after failed medical management and 126 patients who continued with medical treatment only. The primary outcome v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 14 publications
(24 reference statements)
1
51
0
10
Order By: Relevance
“…However, this therapy is only supported by a retrospective series from the Mayo Clinic, which demonstrated that patients with recurrent pericarditis who received surgery experienced fewer relapses than patients with recurrent pericarditis who received medical therapy (level of evidence C). 46 In contrast, a small retrospective study found that few patients (2 of 9 patients) responded to pericardiectomy. 47 Both of these studies are limited by their retrospective design.…”
Section: New Therapeutic Options For Recurrent Pericarditis After Faimentioning
confidence: 94%
“…However, this therapy is only supported by a retrospective series from the Mayo Clinic, which demonstrated that patients with recurrent pericarditis who received surgery experienced fewer relapses than patients with recurrent pericarditis who received medical therapy (level of evidence C). 46 In contrast, a small retrospective study found that few patients (2 of 9 patients) responded to pericardiectomy. 47 Both of these studies are limited by their retrospective design.…”
Section: New Therapeutic Options For Recurrent Pericarditis After Faimentioning
confidence: 94%
“…anakinra) [20][21][22][23][28][29][30][31][32]. Jak udowodniono, u chorych z nawracającym opornym zapaleniem osierdzia istotną alternatywę dla farmakoterapii stanowi perikardiektomia [33]. Opublikowano też wyniki prospektywnych i retrospektywnych badań klinicznych obejmujących duże grupy pacjentów (> 100 osób), dotyczące rokowania i ryzyka rozwoju powikłań u chorych na ostre lub nawracające zapalenie osierdzia [7,9,[34][35][36][37][38].…”
Section: Co Nowego W Chorobach Osierdzia?unclassified
“…W ostateczności można rozważyć wykonanie perikardiektomii, choć zabieg ten można przeprowadzić tylko w przypadku wielokrotnego niepowodzenia farmakoterapii. W tym celu należy pacjenta skierować do ośrodka, gdzie są doświadczeni w tej dziedzinie chirurdzy [33]. Chorych na nawracające zapalenie osierdzia obowiązują takie same ograniczenia aktywności fizycznej jak pacjentów z zapaleniem ostrym [53,54].…”
Section: Leczenieunclassified
See 1 more Smart Citation
“…Case series studies suggest a clinical benefit. 22 Pericardiectomy is not consistently effective, perhaps because visceral pericardium remains after the procedure, along with remnants of parietal pericardium. 3 Patients with cardiac tamponade should undergo urgent therapeutic pericardiocentesis.…”
Section: 14mentioning
confidence: 99%